Ali Кushchi and his scientific legacy - Lafasov Урак (Turkic Studies Journal, 2021)
The article reveals information about the life and work of the medieval scholarencyclopedist Ali Kushji, later called “Ptolemy of his time”. The article reveals the origin story of the scientist as a representative of the genus kutchi, the origins of which the author associates with the Genesis of the later Turkic khanate that is associated with the name Kutlyg Kagan. The author explores the formation of biographical and career of scientist Ali Kushji (kutchi), reveals his training in Samarkand and Iran, the activity of a talented scientist in the school of astronomy of Samarkand, analyzes the contribution of Ali Kushji in the definition of a point latitude, in the update table of the stars “Siji zhaddi Kuragoni”, the scientific activity in China and Turkey. An important place in the article is occupied by the description of comprehensive treatises, especially treatises on mathematics and astronomy, which considers the merit of the scientist in promoting the achievement of the Samarkand school of astronomy to the West.